Blue Optical Observations of Narrow Bipolar Events by ASIM Suggest Corona Streamer Activity in Thunderstorms. Issue 16 (11th August 2020) - Soler, S.; Pérez‐Invernón, F. J.; Gordillo‐Vázquez, F. J.; Luque, A.; Li, D.; Malagón‐Romero, A.; Neubert, T.; Chanrion, O.; Reglero, V.; Navarro‐Gonzalez, J.; Lu, G.; Zhang, H.; et al.
Abstract: While narrow bipolar events (NBEs) could be related with lightning initiation, their intrinsic physics remains in question. Here we report on optical measurements by the Atmosphere‐Space Interactions Monitor (ASIM) on the International Space Station (ISS) of blue flashes associated with NBEs. They are observed in a narrow blue band centered at 337 nm, with no simultaneous activity at 777.4 nm, considered a strong lightning emission line. From radio waves measured from the ground, we find that 7 of 10 single‐pulse blue events can be identified as positive NBEs. The source altitudes estimated from optical and radio signals agree and indicate that the sources of the blue flashes are located between ∼8.5 and ∼14 km, in a cloud reaching 14–15 km altitude. The observations suggest that single‐pulse blue flashes are from cold ionization waves, so‐called streamers, and that positive NBEs are corona discharges formed by many streamers. Plain Language Summary: A special type of cloud electrical discharges called narrow bipolar events (NBEs) could be related with lightning initiation, but their intrinsic physics remains in question. Here we report on optical measurements by the Atmosphere‐Space Interactions Monitor (ASIM) on the International Space Station (ISS) of blue flashes associated with NBEs. They are observed with no simultaneous optical emissions from regular lightning. From radio waves measured from the ground, we find that 70% of the detected single‐pulse blue events can be identified as positive NBEs. The source altitude estimates from optical and radio signals agree and indicate that the sources of the blue events are located between ∼8.5 and ∼14 km inside the thundercloud. The observations suggest that single‐pulse blue flashes are from cold ionization waves, so‐called streamers, and that positive NBEs are corona discharges formed by many streamers. Key Points: ASIM has detected blue flashes associated with positive narrow bipolar events; no simultaneous lightning 777.4 nm emission was recorded Source altitudes derived from optical and radio signals agree and locate NBE and blue flash sources between 8.5 and 14 km inside the cloud Observations suggest that blue flashes are due to streamers, and that positive narrow bipolar events are cloud coronas with many streamers